Coronavirus vaccine acceptance in Ethiopia: Systematic review and meta-analysis - Girma Teferi; Bizunesh Kefale (Elsevier, 2023)
Background: Coronavirus disease was first emerged in China in December 2019 in Wuhan province from patients with pneumonia-like symptoms. It becomes public health and safety threat globally with morbidity and mortality. Prevention is mainly through vaccination of the community to control its burden. This systematic review aimed to assess the level of COVID-19 vaccine acceptance in Ethiopia. Methods: Online searches of articles were conducted using online databases. The online databases used in searching the articles were PubMed, Scopus, Web of Sciences, Google Scholar, and Repository of Universities. This systematic review is reported using the Preferred Reporting Item for Systematic Review and Meta-Analyses (PRISMA) guidelines. Publication biases were checked using funnel plots and Egger tests. Data were extracted into a Microsoft Excel spreadsheet and analyzed using Stata 14. The pooled proportion of COVID-19 vaccine acceptance was computed using random-effects meta-analysis. Subgroup analysis was done by region and population. Result: the review included 35 research articles with 17,348 study participants. In Ethiopia, the overall pooled proportion of COVID-19 vaccine acceptance was 50.92% (95 %CI: 50.24, 51.60). The level of coronavirus vaccine acceptance in Ethiopia shows regional variations. It was 55.27% in Addis Ababa city administration. Relatively the level of acceptance was higher among healthcare workers (59.83%). Conclusion: In Ethiopia, only one-half of the population intends to take the COVID-19 vaccine. The national-level analysis of the misinformation and providing the correct responses can solve the issue, and the community gets coronavirus-related information, which helps them to take the vaccine.